The Relationship Between Smartphone Use and Sleep Quality in Adolescents at Senior High School Negeri 1 Seram Bagian Barat District. Kairatu, West Part of Seram District - Fitriasari, Endah; Umasugi, M Taufan; Soulissa, Fatmhy F; Ibrahim, Ilyas; Rumbouw, Nurlena; Guilin, Xie; Jiao, Deng; Wang, Yuanyuan (Journal of World Future Medicine, Health and Nursing, 2023)
A smartphone is a telephone that is equipped with an internet connection and provides Personal Digital Assistant (PDA) functions such as a calendar, agenda book, calculator, notes, and various sophisticated applications to assist with daily activities. The sophistication and convenience provided by smartphones today causes many people to be trapped in always using smartphones. Excessive smartphone use can have unwanted negative impacts, especially on the health of its users. One of the negative impacts of smartphone use is the disruption of sleep quality. Smartphone use at bedtime can affect sleep quality to be poor, sleep efficiency decreases, and the onset of sleep becomes longer. Smartphones can be habit-forming, in the form of checking habits, repeated checks and the speed of accessing various content using smartphones can affect the increase in smartphone use or addiction. Objective The research was to identify the relationship between smartphone use and sleep quality in adolescents at Senior High School Negeri 1 seram . This research method uses quantitative research with descriptive analytic with Cross Sectional approach. A sample of 213 respondents, using the technique simple random sampling. Analysis data by using the chi square test. The results of the study were based on the chi-square statistical test which refers to the Fisher's Exact Test value, which obtained a p.value of 0.000 where <0.05 indicated that H0 was rejected and Ha was accepted, which means that there is a relationship between smartphone use and sleep quality in adolescents at Senior High School Negeri 1.